Synthesis and Catalytic Reactions of Nanoparticles formed by Electrospray Ionization of Coinage Metals1. Issue 12 (19th February 2014) - Li, Anyin; Luo, Qingjie; Park, So‐Jung; Cooks, R. Graham
Abstract Noble metals can be ionized by electrochemical corrosion and transported by electrospray ionization. Mass spectrometry (MS) showed solvated metal ions as the main ionic constituent of the sprayed droplets. Collection of the electrospray plume on a surface yielded noble metal nanoparticles (NPs) under ambient conditions. The NPs were characterized by several techniques. Under typical conditions, capped‐nanoparticle sizes averaged 2.2 nm for gold and 6.5 nm for silver. The gold nanoparticles showed high catalytic activity in the reduction of p‐nitrophenol by NaBH4. Efficient catalysis was also observed by simply directing the spray of solvated Au+ onto the surface of an aqueous p‐nitrophenol/NaBH4 mixture. Organometallic ions were generated by spiking ligands into the spray solvent: for example, CuI bipyridine cations dominated the spray during Cu electrocorrosion in acetonitrile containing bipyridine. This organometallic reagent was shown to be effective in the radical polymerization of styrene.